The Mechanism of Acupuncture and Moxibustion in Treating Primary Dysmenorrhea was Discussed from the Point of Meridians and Acupoints - Ma, Xiuying; Xiao, Xinchun (Journal of Contemporary Medical Practice, 2024)
The theoretical basis of acupuncture and moxibustion in the treatment of primary dysmenorrhea (PD) is discussed from the perspective of meridians and acupoints. It is pointed out that acupuncture and moxibustion in the treatment of PD is mainly based on the syndrome differentiation of zangfu and meridians, guided by the theory of meridians, and plays a role in balancing Yin and Yang, regulating zangfu and dredging meridians through acupuncture and acupoints. It can improve local blood supply and circulation in the lower abdomen, pelvic cavity and lumbosacral region, and relieve or eliminate pain. In addition, clinical research literature reports that acupuncture and moxibustion or acupuncture combined with other therapies are effective, safe and operable in the treatment of PD, which has certain advantages compared with surgery and drug therapy.